The Effect of Stock Split on Stock Trading Volume and Stock Returns in Companies Listed on the Indonesia Stock Exchange (IDX) in the Years 2020-2023 - Sampe, Defri Agung; Mantong, Augustinus; Wibisono, Lisa Kurniasari (Green Publisher Indonesia, 2024)
This study aims to determine the effect of stock splits on stock trading volume and stock returns in companies listed on the Indonesian stock exchange. The population in this study were 35 companies, 31 of which were used as samples selected by purposive sampling method. The type of data used is secondary data, with the source of company financial report data which includes stock split data, stock trading volume, and stock returns published on the official website of the Indonesian stock exchange. With an observation period of 5 days before and 5 days after the stock split. The data analysis used is a paired sample difference test, namely the Wilcoxon signed rank-test test because the data is not normally distributed. The results showed that stock splits had no significant effect on stock trading volume with a significance value of 0.387> 0.05 while stock splits had a significant effect on stock returns with a significance value of 0.037 <0.05.